Current Trends in Lignocellulosic Bioethanol Production - Dhungana, Pradip; Prajapati, Bikram; Maharjan, Sujeeta; Joshi, Jarina (International Journal of Applied Sciences and Biotechnology, 2022)
In view of crude oil prices, and its environmental issues, utilization of sustainable renewable alternative energies such as biofuels is rapidly progressing in many countries. The increasing global energy demand and depleting fossils fuels sources has led to search alternative clean and renewable fuels. One of the best alternatives to the gasoline is lignocellulosic bioethanol. Recent researches on lignocellulosic bioethanol focuses on advancement of pretreatment techniques for improved sugar yields and decreased inhibitors production. Pretreatment technique with no or less use of chemicals and cost effectiveness is the main purpose of most of the researches. Biological pretreatment techniques produce less fermentation inhibitors than chemical pretreatments. In order to cope with fermentation inhibitors different strategies can be adopted during pretreatment processes. In the course of time, advancements in production process over separate hydrolysis and fermentation have been introduced. Simultaneous saccharification and co/fermentation; and consolidated bioprocessing for bioethanol production are gaining popularity among researchers.Int. J. Appl. Sci. Biotechnol. Vol 10(1): 1-11.